Photocuring conductive hydrogel as well as preparation method and application thereof

Through a preparation method of photocured conductive hydrogel, combined with the preparation steps of crosslinking agent, initiator and comonomer, ultraviolet curing is used for ultraviolet light, which solves the shortcomings of existing conductive hydrogels in terms of conductivity, mechanical properties and biocompatibility, and achieves rapid curing, low-cost and high-performance hydrogels, suitable for multifunctional and industrial applications.

CN119708334APending Publication Date: 2025-03-28NANJING NORMAL UNIVERSITY

Patent Information

Application Number
CN202411858526.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing photocured conductive hydrogels have shortcomings in electrical conductivity, mechanical properties and biocompatibility, and are difficult to meet the needs of multifunctional and industrial applications.

Method used

Through a preparation method of photocuring conductive hydrogel, a hydrogel with excellent conductivity and mechanical properties is prepared by combining zwitterionic monomers, acrylic acid and hydroxyethyl methacrylate, and a photoinitiator and accelerator, to prepare a hydrogel with excellent conductivity and mechanical properties using photoinitiators and accelerators.

Benefits of technology

It realizes rapid curing, low cost, rich raw material sources, good mechanical properties and high conductivity of photocured conductive hydrogels. It is suitable for applications such as flexible sensors and biological signal monitoring, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708334A_ABST
    Figure CN119708334A_ABST
Patent Text Reader

Abstract

The invention discloses photocuring conductive hydrogel as well as a preparation method and application thereof. According to the invention, methacryloylethyl sulfobetaine (SBMA), acrylic acid (AA) and hydroxyethyl methylacrylate (HEMA) are used as comonomers, deionized water is used as a solvent, N, N '-methylenebisacrylamide (MBAA) is used as a cross-linking agent, ammonium persulfate (APS) is used as an initiator, tetramethylethylenediamine (TEMED) is used as an accelerator, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methyl propiophenone (Irgacure2959) is used as a photoinitiator; the conductivity is improved by adding an ionic compound potassium chloride (KCl), and the photocuring conductive hydrogel is prepared in a free radical polymerization manner by adopting an LED-UV curing box. The conductive hydrogel disclosed by the invention has the characteristics of good adhesion property, conductivity, mechanical property and the like, and has wide application in the fields of wearable strain sensors and other flexible electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a photocurable conductive hydrogel and a preparation method and application thereof. Background Art

[0002] Photocurable conductive hydrogel is a new type of material that combines the properties of photocuring technology and conductive hydrogel, and can play an important role in biomedicine, flexible electronics, sensors and other fields. Hydrogel is a three-dimensional polymer network with a high water content that can absorb water and maintain its shape. Their biocompatibility and softness make them widely used in the biomedical field, such as drug delivery, tissue engineering and biosensors. With the rapid development of electronic technology, the demand for flexible and wearable electronic devices has increased dramatically. Conductive hydrogel has become an important research object due to its good mechanical properties and conductivity.

[0003] Photocuring technology is a method that uses a light source (such as ultraviolet light) to cure photosensitive materials in a short time. This technology can accurately control the curing process of materials and quickly prepare complex structures. It is an important means of manufacturing hydrogels. With the advancement of photocuring technology, researchers have gradually applied photocuring methods to the preparation of conductive hydrogels. The research at this stage mainly focuses on how to improve the conductivity, mechanical properties and biocompatibility of materials. In recent years, researchers have begun to develop photocurable conductive hydrogels in a multifunctional direction, such as embedding nanomaterials (such as graphene, carbon nanotubes, etc.) in hydrogels to enhance their conductivity and mechanical strength. At the same time, these materials are used in fields such as biosensors, artificial muscles and soft electronic devices. With the maturity of technology, photocurable conductive hydrogels are gradually moving towards industrialization. Their applications in medical, sports monitoring, environmental monitoring and other fields are constantly expanding, and the market potential is huge. The development of photocurable conductive hydrogels demonstrates the frontier progress of materials science and engineering, and its flexibility and functionality have laid a good foundation for scientific research and application in related fields. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a photocurable conductive hydrogel and a preparation method and application thereof. The hydrogel of the present invention has the advantages of low cost, abundant raw material sources, fast curing time, good mechanical properties, high conductivity, etc.

[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a photocurable conductive hydrogel comprises the following steps:

[0007] Step 1: first prepare a crosslinking agent N,N'-methylenebisacrylamide (MBAA) solution and an initiator ammonium persulfate (APS) solution;

[0008] Step 2: Dissolve zwitterionic methacryloylethyl sulfobetaine in deionized water, and stir magnetically to completely dissolve it in a water bath;

[0009] Step 3: In a water bath environment, add acrylic acid (AA) and hydroxyethyl methacrylate (HEMA) to step 2, and continue to stir the solution, wherein the molar ratio of acrylic acid to hydroxyethyl methacrylate is 1:2-4;

[0010] Step 4: In a water bath environment, add 1 ml of the prepared crosslinking agent N,N'-methylenebisacrylamide solution and 1 ml of the prepared initiator ammonium persulfate solution to the solution obtained in step 3, and continue to stir the solution;

[0011] Step 5: In a water bath environment, 0.001-0.0025 mol of potassium chloride (KCl), a photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and an accelerator tetramethylethylenediamine (TEMED) are added to the mixed solution obtained in step 4 in sequence, and after complete dissolution, magnetic stirring is stopped, and residual bubbles in the solution are removed by ultrasound and centrifugation;

[0012] Step 6: Pour the hydrogel precursor solution obtained in step 5 into a hydrogel mold, place it in an LED-UV curing box for 6 to 7 minutes to complete polymerization, and obtain a light-cured conductive hydrogel.

[0013] As an improvement, in step 1, the concentration of the cross-linking agent N,N'-methylenebisacrylamide solution is 0.016 g / ml, and the concentration of the initiator ammonium persulfate solution is 0.016 g / ml.

[0014] As an improvement, in step 2, the mass of the methacryloylethyl sulfobetaine is 2.6 g, and the volume of deionized water is 2 ml.

[0015] As an improvement, in step 3, the amount of acrylic acid is 0.001 mol, and the amount of hydroxyethyl methacrylate is 0.003 mol.

[0016] As an improvement, in step 4, equal volumes of N,N'-methylenebisacrylamide solution and ammonium persulfate solution are added and mixed.

[0017] As an improvement, in step 5, the amount of KCl is 0.002 mol, the mass of the photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 10 mg, and the volume of the accelerator tetramethylethylenediamine is 10 μl.

[0018] As an improvement, in step 2-5, the water bath temperature is 50° C. and the magnetic stirring rate is 300-700 rpm.

[0019] As an improvement, the material of the hydrogel mold in step 6 is polytetrafluoroethylene, and the specifications are 50mm×10mm×3mm in length, width and height; the hydrogel mold is placed in an LED-UV curing box, 7cm vertically away from the light. The mold should not be too close to the lamp to prevent excessive ultraviolet light intensity from damaging the internal structure of the hydrogel, and the mold should not be too far from the lamp, which will cause more energy loss; a wide wavelength ultraviolet band is used, and the number of lamp beads with two wavelengths of 395nm and 365nm are arranged in the order of 121212...1212.

[0020] The photocurable conductive hydrogel prepared by any of the above preparation methods.

[0021] The photocurable conductive hydrogel prepared by any of the above preparation methods is used in the preparation of flexible strain sensors and biological signal monitoring.

[0022] The photocurable conductive hydrogel of the present invention is prepared by a simple one-pot light-initiated in-situ free radical polymerization. During the polymerization process, the photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone decomposes under ultraviolet light to generate free radicals, thereby initiating the polymerization of comonomers to obtain copolymer chains, thereby preparing a photocurable conductive hydrogel with excellent adhesion, stretchability, transparency and conductive properties.

[0023] Beneficial effects:

[0024] Compared with the prior art, the present invention provides a photocurable conductive hydrogel and its preparation method and application. Photocuring has the advantage of fast reaction speed, and the polymer can be cured in a short time. It also has the advantages of energy saving, environmental protection, high production efficiency, etc. The introduction of ionic compounds can improve the antifreeze performance and conductivity of the photocurable conductive hydrogel, and develop stable hydrogels that can adapt to different application scenarios. Among them, due to the dipole-dipole interaction of zwitterions, the hydrogel can produce adhesion on the surface of various materials up to 32.39Kpa, the strain of mechanical properties can reach 158.25%, the stress can reach 119.55Kpa, the conductivity can reach 1.02S / m, the sensor gauge factor (GF) is about 2.930, and the response time is 0.14s. The prepared photocurable conductive hydrogel has good adhesion, good mechanical properties, excellent conductivity, high sensitivity, fast responsiveness and other advantages, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a surface morphology image of the photocurable conductive hydrogel of Example 3 of the present invention;

[0026] Figure 2A bar graph showing the adhesion properties of the photocurable conductive hydrogels of Examples 1-4 and Comparative Examples 1-3 of the present invention;

[0027] Figure 3 The tensile properties of the photocurable conductive hydrogels of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown;

[0028] Figure 4 The Nyquist plots of the photocurable conductive hydrogels of Examples 1-4 and Comparative Examples 1-3 of the present invention;

[0029] Figure 5 The conductivity diagram of the photocurable conductive hydrogels of Examples 1-4 and Comparative Examples 1-3 of the present invention;

[0030] Figure 6 This is a response time diagram of the photocurable conductive hydrogel of Example 3 of the present invention;

[0031] Figure 7 This is a gauge factor diagram of the photocurable conductive hydrogel of Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0033] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described can be obtained from commercial sources or simply prepared by existing technologies unless otherwise specified.

[0034] Example 1

[0035] Under 50°C water bath conditions, 2.6g of zwitterionic monomer methacryloylethyl sulfobetaine (SBMA) was weighed and dissolved in 2ml of deionized water. After it was completely dissolved, 0.072g of acrylic acid (AA) and 0.39g of hydroxyethyl methacrylate (HEMA) were added in sequence and continued to stir. Subsequently, 1ml of crosslinker MBAA (0.016g / ml) solution and 1ml of initiator APS (0.016 / ml) solution, 0.001mol of potassium chloride (KCl), 0.01g of photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and 0.01mol of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were added. The accelerator TEMED 10 μl was added, and a uniform hydrogel precursor solution was obtained by ultrasonic defoaming. The precursor solution was poured into a polytetrafluoroethylene (PTFE) hydrogel mold 50 mm×10 mm×3 mm (length×width×height), and placed in a LED-UV curing box (power consumption 240 W, UVG01600, Guangdong Zhongshan Yanxi Zao Lighting Appliance Factory) at a height of about 7 cm from the light. The lamp beads with a wide wavelength in the ultraviolet band and two wavelengths of 395 nm and 365 nm were arranged in the order of 121212...1212, and the irradiation time was 6 min to obtain the light-cured conductive hydrogel.

[0036] Example 2

[0037] Except that the amount of potassium chloride was changed to 0.0015 mol, the rest was the same as in Example 1.

[0038] Example 3

[0039] Except that potassium chloride was changed by 0.002 mol, the rest was the same as in Example 1.

[0040] Example 4

[0041] The same as in Example 1 except that the amount of potassium chloride was changed to 0.0025 mol.

[0042] Comparative Example 1

[0043] Under 50°C water bath conditions, 2.6g of zwitterionic monomer SBMA was weighed and dissolved in 2ml of deionized water. After it was completely dissolved, 0.072g of acrylic acid (AA) and 0.26g of hydroxyethyl methacrylate (HEMA) were added in sequence and continued to stir. Subsequently, 1ml of crosslinker MBAA (0.016g / ml) solution and 1ml of initiator APS (0.016 / ml) solution, 0.01g of photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and 10μl of accelerator TEMED were added. The mixture was stirred by ultrasonication. Defoaming was performed to obtain a uniform hydrogel precursor solution, and the obtained precursor solution was poured into a polytetrafluoroethylene (PTFE) hydrogel mold of 50 mm × 10 mm × 3 mm (length × width × height), and placed in a LED-UV curing box (power consumption 240 W, UVG01600, Guangdong Zhongshan Yanxi Zao Lighting Appliance Factory) at a height of about 7 cm from the light. An ultraviolet wide wavelength lamp bead with two wavelengths of 395 nm and 365 nm was used, and the number of lamp beads was arranged in the order of 121212...1212, and the irradiation time was 6 min to obtain a light-cured conductive hydrogel.

[0044] Comparative Example 2

[0045] The same procedures as in Comparative Example 1 were followed except that the amount of hydroxyethyl methacrylate (HEMA) was changed to 0.39 g.

[0046] Comparative Example 3

[0047] The same procedures as in Comparative Example 1 were followed except that the amount of hydroxyethyl methacrylate (HEMA) was changed to 0.52 g.

[0048] Performance Testing

[0049] The tensile strength, peel strength and electrical conductivity of the photocurable conductive hydrogels prepared in Examples 1-4 and Comparative Examples 1-3 were characterized as follows.

[0050] Tensile strength characterization method: A universal electronic tensile testing machine was used to make the hydrogel sample into a long strip shape using a polytetrafluoroethylene mold with a specification size of (50mm×10mm×4mm). The original gauge length, i.e., the effective tensile length, was set to 40mm, and the tensile rate was set to 50mm / min. At least five samples of different hydrogel components were prepared to ensure that multiple repeated tests could be performed to reduce the test error.

[0051] Peel strength characterization method: Pig skin and human skin have biological similarities and are considered to be representative experimental materials close to human skin. The adhesion strength of the hydrogel was measured by the pig skin shear adhesion test. The prepared hydrogel was cut into 1 cm × 1 cm squares with an area of ​​1 cm 2, evenly adhered to the surface of the pretreated long pig skin (6cm×2cm), the two pieces of pig skin were glued tightly, a 1kg weight was placed at the bonding position and placed in an electric heating blast drying oven at 37℃ for 0.5h. The adhesion strength of the hydrogel was tested using a universal electronic tensile machine with a peel strength scheme, and the test speed was 10mm / min. Three parallel experiments were set for each sample.

[0052] Conductivity performance characterization method: The hydrogel was made into a small cylinder with a radius of 15 mm and a thickness of 5 mm, and sandwiched between two conductive copper sheets. The electrochemical impedance spectroscopy of the hydrogel was tested using an electrochemical workstation. The open circuit potential of the hydrogel was first tested. -1 ~10 5 In the Hz frequency range, the voltage of the electrochemical workstation was set to 5mv, the Nyquist plot was obtained by testing, and the conductivity was calculated by the formula.

[0053] The above test results are shown in Table 1.

[0054] Table 1 Characterization of various properties of conductive hydrogels prepared under different parameters

[0055] Stress(KPa) Adhesion strength(KPa) Impedance(Ω) Conductivity (S / m) Example 1 70.4 12.01 63.9 0.6261 Example 2 60.58 12.6 58.33 0.783 Example 3 56.78 10.89 32.7 1.012 Example 4 58.35 11.25 37.92 0.879 Comparative Example 1 78.2 32.39 594.9 0.068 Comparative Example 2 87.13 21.381 540.7 0.074 Comparative Example 3 119.75 24.75 551.2 0.065

[0056] As can be seen from Table 1, the photocurable conductive hydrogel prepared by the present invention has good mechanical properties, good adhesion (meeting adhesion requirements), and excellent conductivity. When the ionic compound potassium chloride is introduced, it can be found that the conductivity of Examples 1-4 is 10 times higher than that of Comparative Examples 1-3, giving the hydrogel high conductivity. Among them, Example 3 has the lowest impedance and the highest conductivity. The gauge factor (GF) of the conductive hydrogel used as a strain sensor is tested to be about 2.930, and the response time can reach 0.14s, which can meet the requirements of flexible sensors.

[0057] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a photocurable conductive hydrogel, characterized in that: The following steps are involved: Step 1: first prepare a crosslinking agent N,N'-methylenebisacrylamide solution and an initiator ammonium persulfate solution; Step 2: Dissolve zwitterionic methacryloylethyl sulfobetaine in deionized water, and stir magnetically to completely dissolve it in a water bath; Step 3: In a water bath environment, add acrylic acid and hydroxyethyl methacrylate to step 2, and continue to stir the solution, wherein the molar ratio of acrylic acid to hydroxyethyl methacrylate is 1:2-4; Step 4: In a water bath environment, add 1 ml of the prepared crosslinking agent N,N'-methylenebisacrylamide solution and 1 ml of the prepared initiator ammonium persulfate solution to the solution obtained in step 3, and continue to stir the solution; Step 5: In a water bath environment, 0.001-0.0025 mol of potassium chloride, a photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and an accelerator tetramethylethylenediamine are added to the mixed solution obtained in step 4 in sequence, and after complete dissolution, magnetic stirring is stopped, and residual bubbles in the solution are removed by ultrasound and centrifugation; Step 6: Pour the hydrogel precursor solution obtained in step 5 into the hydrogel mold, place it in an LED-UV curing box for 6 to 7 minutes to complete polymerization, and obtain a light-cured conductive hydrogel.

2. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 1, the concentration of the cross-linking agent N,N'-methylenebisacrylamide solution is 0.016 g / ml, and the concentration of the initiator ammonium persulfate solution is 0.016 g / ml.

3. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 2, the mass of the methacryloylethyl sulfobetaine is 2.6 g, and the volume of deionized water is 2 ml.

4. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 3, the amount of acrylic acid is 0.001 mol, and the amount of hydroxyethyl methacrylate is 0.003 mol.

5. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 4, equal volumes of N,N'-methylenebisacrylamide solution and ammonium persulfate solution are added and mixed.

6. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 5, the amount of KCl is 0.002 mol, the mass of the photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 10 mg, and the volume of the accelerator tetramethylethylenediamine is 10 µl.

7. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 2-5, the water bath temperature is 50° C., and the magnetic stirring rate is 300-700 rpm.

8. The method for preparing a photocurable conductive hydrogel according to claim 1, characterized in that: In step 6, the material of the hydrogel mold is polytetrafluoroethylene, and the specifications are 50mm×10mm×3mm in length, width and height; the hydrogel mold is placed in the LED-UV curing box, 7cm vertically away from the light, and uses a wide wavelength in the ultraviolet band, and the number of lamp beads with two wavelengths of 395nm and 365nm are arranged in the order of 121212...1212.

9. A photocurable conductive hydrogel prepared by any one of the preparation methods of claims 1 to 8.

10. Application of the photocurable conductive hydrogel prepared by any one of the preparation methods of claims 1 to 8 in the preparation of flexible strain sensors and biological signal monitoring.

Citation Information

Patent Citations

  • Self-healing sulfobetaine zwitterionic nano composite aquagel and preparation method thereof

    CN104497208A

  • Hydrogel, composition for preparation of hydrogel and preparation method of hydrogel

    CN106750377A

  • Preparation method and application of anti-swelling zwitterionic hydrogel sensing material with controllable rehydration and high strain sensitivity

    CN113968981A

  • Natural polymer conductive hydrogel as well as preparation method and application thereof

    CN114805673A

  • Zwitterionic Anti-freezing organic hydrogel, preparation method therefor, and use thereof

    WO2023004930A1

Cited By

  • Anti-swelling high-adhesion hydrogel strain sensor for underwater monitoring and preparation method thereof

    CN120445023A

  • Anti-swelling, highly adhesive hydrogel strain sensor for underwater monitoring and its preparation method

    CN120445023B

  • Method for rapidly and quantitatively detecting conductivity of photocuring conductive hydrogel

    CN121678771A